KNOWLEDGE AND ATTITUDES OF PREGNANT WOMEN TOWARDS THE BEHAVIOR OF USING ULTRASONOGRAPHY IN PREGNANCY EXAMINATION AT THE MAIN INPATIENT CLINIC OF SRI HARTI SOEROSO, SURABAYA CITY - Wulandari, Anggrawati; Linda Lutfiyatus Sholika (Journal for Research in Public Health, 2025)
The highs and lows of the problem are caused by lack of knowledge and attitudes toward behavior of using ultrasound in pregnancy checks. Influencing factors are factors related to use by pregnant women, including knowledge, attitudes and behavior of pregnant women. The aim of this study was to determine the relationship between knowledge, attitudes and behavior of pregnant women and the use of ultrasound in pregnancy examinations. The aim of this research is to determine the level of knowledge of pregnant women about Ultrasonography and their use of behavior to support pregnancy examinations.This research uses descriptive research with a cross sectional approach located in the city of Surabaya, East Java. The research sample was 20 people taken using the Accidental Sampling technique. Data collection was carried out using a questionnaire. The data analysis technique used in this research is: Chi – Square. The results of this research show that 70% of pregnant women have good knowledge. The results of research in the attitude category were 65% in the good category, and the results of behavioral research were 55% in the good category regarding the use of ultrasound in pregnancy checks. The results of data analysis show that p value of 0.000 is less than 0.05, meaning there is a significant relationship between knowledge and attitudes in the behavior of using ultrasound. Based on the research results, it was concluded that the good knowledge possessed by pregnant women is supported by the attitudes and behavior of mothers who always carry out routine ultrasound examinations so that the health of the mother and fetus can be known well.